Maker pro - Altman, Mitch, 1956-; Baichtal, John, ....- (Sebastopol : Maker Media, 2015)
Maker Pro is a book of essays by more than a dozen prominent and up-and-coming professional makers (Maker Pros). Each essay includes advice and stories on topics such as starting a kit-making business, taking a hardware project open-source, and plenty of encouragement to "quit your day job." This book is a reference for anyone who dreams of turning a hobby into a small business, and features stories from well-known professional makers; it will turn aspiration into inspiration.
"Edited by John Baichtal ; foreword by Joey Hudy"--Cover.
Includes index.
"Make: makezine.com"--Back cover.
Keywords: New business enterprises